The scholar as reader: the last 50 years of economic theory seen through G.C. Harcourt's book reviews. (7th February 2013) - Repapis, Constantinos
Abstract: G.C. Harcourt has written over 100 book reviews during the last 50 years. These are published in a number of journals and on widely different topics. In this article this literature is used in order to discuss three important issues. (i) How did Harcourt engage with the developments in economic theory across the different schools in economics during this period? (ii) What do these book reviews tell us about how Harcourt does economics? (iii) Why is this reviewing activity such an important part of Harcourt's research activity and what does this tell us about the structure of post-Keynesian economics? This article argues that book reviews as well as review articles are a constitutive element of how Harcourt does economics, as they organise different and occasionally disparate theoretical contributions into a coherent narrative that gives form and substance to his theoretical approach.